Deuterium‐depleted water: A new tracer to label pulmonary surfactant lipids in adult rabbits. (21st January 2022) - Simonato, Manuela; Ricci, Francesca; Catozzi, Chiara; Storti, Matteo; Giambelluca, Sonia; Correani, Alessio; Salomone, Fabrizio; Cogo, Paola; Carnielli, Virgilio
Abstract: Stable isotope tracing can be safely used for metabolic studies in animals and humans. The endogenous biosynthesis of lipids (lipogenesis) is a key process throughout the entire life but especially during brain and lung growth. Adequate synthesis of pulmonary surfactant lipids is indispensable for life. With this study, we report the use of deuterium‐depleted water (DDW), suitable for human consumption, as metabolic precursor for lipogenesis. We studied 13 adult rabbits for 5 days. Four rabbits drank tap water (TW) and served as controls; in four animals, DDW was substituted to drinking water, whereas five drank deuterium‐enriched water (DEW). After 5 days, a blood sample and a bronchoalveolar lavage (BAL) sample were collected. The 2 H/ 1 H (δ 2 H) of BAL palmitic acid (PA) desaturated phosphatidylcholine (DSPC), the major phospholipid of pulmonary surfactant, and of plasma water was determined by high‐resolution mass spectrometry. We found that the δ 2 H values of DDW, DEW and TW were −984 ± 2‰, +757 ± 2‰ and −58 ± 1‰, respectively. After 5 days, plasma water values were −467 ± 87‰, +377 ± 56‰ and −53 ± 6‰, and BAL DSPC‐PA was −401 ± 27‰, −96 ± 38‰ and −249 ± 9‰ in the DDW, DEW and TW, respectively. With this preliminary study, we demonstrated the feasibility of using DDW to label pulmonary surfactant lipids. This novel approach can be used in animals and in humans, and we speculate that it could be associated with more favourable study compliance than DEW in human studies.